Al-Kafââ't al-Tarbawiyyah Li Mu'allimî al-Lughah al-'Arabiyyah Fî Tahtîth al-Ta’lîm wa Tanfîdzuhu Fî Madrasah Miftah al-‘Ulum al-Muthawassithah bi Madiun - Jamaluddin Shiddiq (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2021)
This study aims to determine the pedagogic competencies of Arabic language teachers at Madrasah Tsanawiyah Miftahul Ulum Madiun which have an impact on the ability to compose and implement effective learning. This research includes field research with a qualitative-descriptive approach. The research objects are teachers and school principals using research instruments including observation, interviews, and documentation. The results showed that first, the Arabic language teacher at Madrasah Tsanawiyah Miftahul Ulum Madiun has qualifications and backgrounds that are in accordance with his profession. Second, Arabic teachers have the ability to develop lesson plans and understand the importance of preparing learning plans well. And third, the maximum pedagogical competence possessed ultimately affects the quality learning process for students, and learning becomes fun and the assessment of learning by teachers is able to describe the linguistic development of students in a general.